The Influence of Good Corporate Governance on Tax Aggressiveness in Mining Companies in Indonesia - Siahaan, Trioksa; Unjaini , Feri Asandi (Economics and Business Journal (ECBIS), 2024)
This study aims to analyze the impact of Good Corporate Governance (GCG) on tax aggressiveness in mining companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach was used in this research, with secondary data obtained from financial statements and annual reports of companies over a certain period. The results show that GCG, particularly independent board commissioners and the frequency of board meetings, has a negative and significant impact on tax aggressiveness. However, the influence of the audit committee and the nomination and remuneration committee on tax aggressiveness is not significant. These findings underscore the importance of stronger GCG implementation to reduce risks associated with corporate tax policies. This study provides important implications for companies and regulators in enhancing effective corporate governance to reduce tax aggressiveness in the mining sector.